The Ciji-Hua’ai-Baosheng II Formula Attenuates Chemotherapy-Induced Anorexia in Mice With H22 Hepatocellular Carcinoma - Xi, Shengyan; Zhai, Xiangyang; Wang, Yanan; Gong, Yuewen; Fu, Biqian; Gao, Chunling; Guo, Xuehui; Li, Yunhong; Wang, Zheng; Huang, Shuqiong; Lu, Dawei; Zhao, Yufang; et al. (Frontiers in Pharmacology, 2021)
CHB-II-F is a traditional Chinese medicine formula, which specifically targets on different aspects of chemotherapy induced adverse effects in patients with cancer. However, the mechanism of CHB-II-F in alleviation of chemotherapy-induced anorexia remains to be further investigated. To explore the therapeutic effect and mechanism of CHB-II-F on chemotherapy-induced anorexia in the mice model of H22 hepatoma, a total of 72 Kunming mice of SPF grade were inoculated with H22 hepatoma cells into the right anterior armpit. After one week of seeding, mice were injected intraperitoneally with 5-FU (200 mg/kg) to establish the model of chemotherapy. The mice were randomly divided into 6 groups: untreated, 5-FU, 5-FU plus Yangzheng Xiaoji Capsule and three groups of 5-FU plus different concentrations of CHB-II-F. All the mice were treated for 14 days. The body weight, food intake, tumor volume and tumor weight of mice, pathological examinations of tumor tissue, stomach and duodenum, expressions of serum Leptin, NPY, EGF, MTL, OXA, GAS, Ghrelin, PGE2, SOD activity and MDA content, protein and mRNA levels of POMC, OX1R, NPY, CART, AgRP, Ob-R and GHSR in hypothalamus, and the protein levels of SP and 5-HT in duodenum were documented. Results showed that combination of CHB-II-F and 5-FU could enhance the inhibitory effect of 5-FU on tumor. Compared with untreated and 5-FU groups, CHB-II-F significantly increased the body weight and food intake of tumor-bearing mice, increased the content of NPY, Orexin A, Ghrelin, GAS, MTL, EGF, PGE2 in serum and the activity of SOD in jejunum, decreased the content of Leptin in serum and the content of MDA in jejunum, enhanced the expression of OX1R, GHSR, NPY, AgRP protein and gene, decreased the expression of Ob-R, POMC, CART protein and gene in hypothalamus of mice, and decreased the expression of 5-HT and SP protein in duodenum. So in the mouse model of H22 receiving chemotherapy, CHB-II-F enhances the inhibitory effect of 5-FU on tumor, significantly improves the pathological injury of gastrointestinal tract caused by chemotherapy. It may alleviate chemotherapy-induced anorexia by affecting appetite regulatory factors in the feeding area of hypothalamus central nervous system and peripheral appetite regulatory factors.